2012
DOI: 10.7748/en2012.02.19.9.31.c8943
|View full text |Cite
|
Sign up to set email alerts
|

Are emergency care staff prepared for disaster?

Abstract: When disasters occur, nurses of all specialties require the appropriate knowledge and skills to respond effectively and efficiently. To assess the extent to which nurses in the US are prepared for emergencies, researchers have developed the Emergency Preparedness Information Questionnaire (EPIQ), in which participants are invited to assess their familiarity with aspects of emergency preparedness. This article discusses a pilot study of the use of the EPIQ among minor injury unit nurses and healthcare assistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 0 publications
1
35
0
Order By: Relevance
“…Broadly, some studies identified that either clinical or technical disaster skills combined with structural disaster knowledge are important 5 9 , 16 , 21 , 24 Some studies focused on only clinical or technical disaster preparedness 6 16 , 29 , 33 Additionally, some studies identified that content could be based on national or international competencies 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, some studies identified that either clinical or technical disaster skills combined with structural disaster knowledge are important 5 9 , 16 , 21 , 24 Some studies focused on only clinical or technical disaster preparedness 6 16 , 29 , 33 Additionally, some studies identified that content could be based on national or international competencies 20 …”
Section: Resultsmentioning
confidence: 99%
“…, 9 , 16 , 21 , 24 Some studies focused on only clinical or technical disaster preparedness 6 16 , 29 , 33 Additionally, some studies identified that content could be based on national or international competencies 20 25 , 33 , 38 , 39 The methods of disaster preparedness programs included online learning, didactic, self-learning, disaster exercises, or blended learning involving more than one method of teaching or learning.…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Worrall ( 28 ), nurses obtained the highest scores in biological agent and lowest scores in ICS. McKibbin et al ( 29 ) also showed that familiarity of nurses in disaster preparedness were in low.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study among nurses showed that participants had a low perception of their preparedness for disaster management (28). Hence, for effective disaster training and educational programmes, HCPs' awareness and understanding should be fully explored and described to present a real picture of the current status of their disaster preparedness (29).…”
Section: Discussionmentioning
confidence: 99%